Modeling Leidenfrost drops over heated liquid substrates. (January 2019) - Qiao, Long; Zeng, Zhong; Xie, Haiqiong; Liu, Hao; Zhang, Liangqi
Highlights: A model of evaporation process within a three-fluid system is established. A new lattice Boltzmann model is proposed for the axisymmetric flow. The Leidenfrost state of drops over heated liquid substrates is modeled. The effects of several parameters on the Leidenfrost drops are unveiled. Abstract: To simulate Leidenfrost drops over a heated liquid pool (namely the liquid-substrate-based (LSB) Leidenfrost drops), a model of evaporation phase change contained within a three-fluid system is developed based on the ternary Cahn-Hilliard equations. In the numerical simulation, an axisymmetric model employing a hybrid LB-FD (lattice Boltzmann-finite difference) method is established, and the model and code are validated by two classical problems, i.e. lens spreading and drop evaporation. Then, the dynamics of LSB Leidenfrost droplets is unveiled numerically, and the results firstly present the distribution of evaporation flux, temperature and velocity near the LSB Leidenfrost drop. Meanwhile, this study also addresses the influence of several important parameters (including vapor Stefan number, vapor Prandtl number, drop Bond number, drop Ohnesorge number, releasing height and pool depth) on the evolution of drop volume and the configuration of quasi-equilibrium Leidenfrost system.